The Influence Of Work Culture, Morality and Leadership on Performance Mediated by Organizational Commitment In Employees PLN UP2D Aceh - Agung Saputra; Mesra B; Elfitra Desi (Equivalent : Journal of Economic, Accounting and Management, 2026)
The purpose of this study was to investigate the impact of Ethical Work Culture and Leadership on Employee Performance, with Organizational Commitment as a mediating factor for employees at PLN UP2D Aceh. A quantitative methodology was adopted, and data were collected through a survey administered to 41 participants. The analysis used Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine the direct and indirect correlations between the study variables. The findings indicate that Ethical Work Culture positively contributes to Employee Performance and Organizational Commitment, while Leadership significantly influences Organizational Commitment but has no direct impact on Employee Performance. Furthermore, it was shown that Organizational Commitment acts as a mediator in the influence of Ethical Work Culture and Leadership on Employee Performance. These results emphasize that fostering a work environment based on ethical principles and strong leadership is crucial for improving employee performance by strengthening organizational commitment.